Surgical Management of a Rare Complex Periprosthetic Fracture of Tibia in a Young Patient – Case Report and a Novel Technique - Dilbans Singh Pandher; Nitish Khosla (Journal of Orthopaedic Case Reports)
Introduction: Periprosthetic fractures of tibia are rarer form of injury after total knee arthroplasty. Most of these fractures occur in elderly patients with osteoporotic bones. Poor bone quality, age, and comorbidities restrict the management options for these fractures to constrained knee or megaprosthesis. However, in younger age group patients, considering the short survival of constrained or mega knee prosthesis in comparison to primary knee, every attempt should be made to restore the primary knee. Case Report: We report the case of a rare combination type periprosthetic tibial fracture, that is, Felix Type 1B with Felix Type 4, in a 47-year-old female. Considering the young age of the patient and thus good bone quality, we planned for restoration of tibia with bone grafts while revising the tibial component with stemmed tibial base plate, and preserving the cruciate retaining femoral component. The avulsed tibial tuberosity was fixed with cerclage wire looped around the tibial stem. Patient was kept non-weight bearing for 4 weeks, followed by partial weight-bearing for next 6 weeks. Bone grafts were fully incorporated at the final follow-up. Patient had 0–110° range of motion with no limp or laxity in the operated limb. Conclusion: We conclude that in patients with good bone quality, even if a small part of the tibial plateau is preserved, stemmed tibia with reconstruction of the tibial plateau should be considered as an option to manage the Type 1B fractures, since these patients have high potential for osteointegration of the grafts and restoration of the primary knee will definitely have longer survival than constrained or mega knee prosthesis.